The Correlation Between Material Knowledge with the Incidence of ISPA in Toddlers at UPTD Puskesmas Pahandut Palangka Raya - Gustriana Tasia; Mariaty A. Sangkai; Anggreni Ade Putri (PROMOTOR, 2026)
Background: Acute Respiratory Infection (ARI) is an infection that affects the upper and lower respiratory tract, including nose, throat, sinuses, bronchi, and lungs. ISPA can be caused by a variety of viruses and bacteria, with common symptoms such as cough, runny nose, sore throat, and fever. Mother's knowledge plays an important role in preventing and treating ISPA in toddlers, mothers are closer in the care of toddlers and families. Objective: To find out the correlation between maternal knowledge with the incidence of ISPA in toddlers at UPTD Puskesmas Pahandut Palangka Raya. Method: Quantitative with a cross sectional approach. The total population was 3,323 people with the research sample of 97 respondents, specifically mothers who have toddlers 1-5 years old. The sample collection technique used accidental sampling. The Data was collected using questionnaires. The Data analysis was carried out by using the Chi-Square test. Results: The Result showed that there was a significant correlation between the level of knowledge of the mother and the incidence of ISPA in toddlers (p value = 0.002 or p<0.05). Mothers with less knowledge were likely to have a toddler who had experienced ISPA in toddlers. Conclusion: There was a correlation between the level of knowledge of mothers and the incidence of ISPA in toddlers at the UPTD Puskesmas Pahandut Palangka Raya. Continuous education is needed to increase maternal knowledge in efforts to prevent ISPA in toddlers.